A distinct impact of repeated morphine exposure on synaptic plasticity at Schaffer collateral‐CA1, temporoammonic‐CA1, and perforant pathway‐dentate gyrus synapses along the longitudinal axis of the hippocampus. Issue 1 (13th December 2022) - Anvari, Sohrab; Foolad, Forough; Javan, Mohammad; Mirnajafi‐Zadeh, Javad; Fathollahi, Yaghoub
Abstract: We aimed to study how morphine affects synaptic transmission in the dentate gyrus and CA1 regions along the hippocampal long axis. For this, recording and measuring of field excitatory postsynaptic potentials (fEPSPs) were utilized to test the effects of repeated morphine exposure on paired‐pulse evoked responses and long‐term potentiation (LTP) at Schaffer collateral‐CA1 (Sch‐CA1), temporoammonic‐CA1 (TA‐CA1) and perforant pathway‐dentate gyrus (PP‐DG) synapses in transverse slices from the dorsal (DH), intermediate (IH), and ventral (VH) hippocampus in adult male rats. After repeated morphine exposure, the expression of opioid receptors and the α1 and α5 GABAA subunits were also examined. We found that repeated morphine exposure blunt the difference between the DH and the VH in their basal levels of synaptic transmission at Sch‐CA1 synapses that were seen in the control groups. Significant paired‐pulse facilitation of excitatory synaptic transmission was observed at Sch‐CA1 synapses in slices taken from all three hippocampal segments as well as at PP‐DG synapses in slices taken from the VH segment in the morphine‐treated groups as compared to the control groups. Interestingly, significant paired‐pulse inhibition of excitatory synaptic transmission was observed at TA‐CA1 synapses in the DH slices from the morphine‐treated group as compared to the control group. While primed‐burst stimulation (a protocol reflecting normal neuronal firing) induced a robust LTP in hippocampal subfields in all control groups, resulting in a decaying LTP at TA‐CA1 synapses in the VH slices and at PP‐DG synapses in both the IH and VH slices taken from the morphine‐treated rats. In the DH of morphine‐treated rats, we found increased levels of the mRNAs encoding the α1 and α5 GABAA subunits as compared to the control group. Taken together, these findings suggest the potential mechanisms through which repeated morphine exposure causes differential changes in circuit excitability and synaptic plasticity in the dentate gyrus and CA1 regions along the hippocampal long axis.